Bisexual, pansexual, queer: Non-binary identities and the sexual borderlands - Callis, April Scarlette (Sexualities, 2014)
This article focuses on sexualities in the USA that exist within the border between heterosexuality and homosexuality. I first examine the usefulness of applying borderland theory to non-gay/non-straight sexualities such as queer and bisexual. I then give an ethnographic analysis of sexual self-identities on the borders, shedding light on how participants envisioned labels such as ‘pansexual,’ and ‘heteroflexible.’ Finally, I explore the ways that the sexual borderlands became tangible in Lexington, Kentucky at certain events and locations. Throughout, I highlight the ways that the sexual borderland touches on all sexualities, as individuals knowingly cross, inhabit, or bolster sexual identity borders.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; discipline; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques; états-unis; étude qualitative

Queering borders: Language, sexuality and migration - Murray, David A.B. (Journal of Language and Sexuality, 2014)
Preface to the special issue on queering borders in the journal of language and sexuality.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; histoire et politique; identités LGBTQIA2+; migration; migrations queer; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques